Parasitaemia and Its Relation to Hematological Parameters and Liver Function among Patients Malaria in Abs, Hajjah, Northwest Yemen - Al-Salahy, Mohamed; Shnawa, Bushra; Abed, Gamal; Mandour, Ahmed; Al-Ezzi, Ali (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Plasmodium falciparum malaria is the most common infection in Yemen. The present study aims to investigate changes in hematological and hepatic function indices of P. falciparum infected individuals. This study included 67 suspected falciparum malarial patients attended in clinics and rural Abs Hospital (Tehama, Hajjah), Yemen, from October 2013 to April 2014. The diagnosis of malaria was confirmed by thick and thin film with Giemsa staining of malaria parasite. Hematological parameters and serum levels of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and bilirubin (total and direct) as test indicators of liver function were studied. Patients with parasitaemia tended to have significantly lower hemoglobin, hematocrit, white blood cell count, lymphocytes, and platelets, compared with healthy normal subjects. Neutrophils levels were significantly higher in cases of falciparum malaria in comparison to healthy normal subjects. Serums AST, ALT, ALP, and bilirubin (total and direct) in falciparum malaria patients were significantly higher (p<0.0001) than those of falciparum malaria of free individuals. Hematological and liver dysfunctions measured parameters were seen associated with moderate and severe parasitaemia infection. This study concludes that hematological and hepatic dysfunction parameters could be indicator of malaria in endemic regions.